2021
DOI: 10.1186/s12943-021-01460-1
|View full text |Cite
|
Sign up to set email alerts
|

IRAK1-regulated IFN-γ signaling induces MDSC to facilitate immune evasion in FGFR1-driven hematological malignancies

Abstract: Background Stem Cell leukemia/lymphoma syndrome (SCLL) presents as a myeloproliferative disease which can progress to acute myeloid leukemia and is associated with the coincident development of B-cell and T-cell lymphomas. SCLL is driven by the constitutive activation of fibroblast growth factor receptor-1 (FGFR1) as a result of chromosome translocations with poor outcome. Mouse models have been developed which faithfully recapitulate the human disease and have been used to characterize the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…One factor likely contributing to the discrepancy between our findings and those identified in Mecp2 Tg3 mice may be the role of IRAK1, overexpressed at both transcript and protein level in the Mecp2 Dup mice, which is unaccounted for by previous models. IRAK1 signaling was previously shown to cause Th1 differentiation via induction of T-bet (Cai et al, 2021; Deng et al, 2003; Heiseke et al, 2015). Additionally, increased IRAK1 expression in the context of Behcet’s disease was associated with increased production of IFNγ (Sun et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…One factor likely contributing to the discrepancy between our findings and those identified in Mecp2 Tg3 mice may be the role of IRAK1, overexpressed at both transcript and protein level in the Mecp2 Dup mice, which is unaccounted for by previous models. IRAK1 signaling was previously shown to cause Th1 differentiation via induction of T-bet (Cai et al, 2021; Deng et al, 2003; Heiseke et al, 2015). Additionally, increased IRAK1 expression in the context of Behcet’s disease was associated with increased production of IFNγ (Sun et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Tumour‐secreted type I and II IFNs have promoted Tregs proliferation and expansion and PD‐L1 expression on tumour cells, promoting tumour progression in MM tumours 49,50 . Moreover, mounting evidence has focused on the association between IFN signalling and MDSC induction 51–53 . The underlying mechanism directing the opposite functions of IFN signalling is unknown; however, its immunosuppressive function is critical as a negative feedback force to protect the host from excessive immune stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 Moreover, mounting evidence has focused on the association between IFN signalling and MDSC induction. [51][52][53] The underlying mechanism directing the opposite functions of IFN signalling is unknown; however, its immunosuppressive function is critical as a negative feedback force to protect the host from excessive immune stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the binding sequence of circFECR1 to the FLI1 promoter contained abundant CpG islands. The further mechanistic studies found that circFECR1 could bind the promoter region of DNMT1 (DNA methyltransferase 1), a methyltransferase essential for maintaining DNA methylation, to downregulate DNMT1 transcription ( 57 ). The transcriptional regulatory capacity caused by DNA methylation was usually co-regulated by DNA methyltransferase and DNA demethylase, circFECR1 was also found to recruit the DNA demethylase TET1 (tet methylcytosine dioxygenase 1) in the promoter region of the host gene FLI1 to directly induce DNA demethylation of the parent gene, thereby regulating the transcriptional activity of the target gene FLI1 ( 58 ).…”
Section: The Role and Molecular Mechanisms Of Circrnas Regulating Par...mentioning
confidence: 99%